2010
DOI: 10.1111/j.1468-3083.2009.03476.x
|View full text |Cite
|
Sign up to set email alerts
|

Nail changes in patients with liver disease

Abstract: Nail changes are observed with not only liver cirrhosis but also with HCV and HBV infection, and this will add additional clinical criteria for general practitioners and dermatologists to help them with diagnosis of these common systemic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Nail changes were seen in 72% of patients. Salem et al 13 2010 in his study showed that nail changes were present in 68% of patients. The most common being Terry's nail seen in 75 % cases.…”
Section: S No Etiology Of Liver Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…Nail changes were seen in 72% of patients. Salem et al 13 2010 in his study showed that nail changes were present in 68% of patients. The most common being Terry's nail seen in 75 % cases.…”
Section: S No Etiology Of Liver Diseasementioning
confidence: 93%
“…Onychomycosis was seen in 50% cases as second common manifestation. Salem et al 13 in his study showed that among nail changes: onychomycosis was the most common finding seen in 18% cases followed by in descending order, longitudinal striations, brittle nails, clubbing of nails, dystrophic nails, leukonychia and longitudinal melanonychia. Leukonychia, brittle nails and clubbing was seen in 12.…”
Section: S No Etiology Of Liver Diseasementioning
confidence: 96%
“…Salem et al and Gavli et al in their studies showed nail changes in 68% and 72% of patients respectively. 15,19 The most common finding in our study was Terry's nails, seen in 17% cases, followed by longitudinal ridging which was seen in 16% of the patients. Other major findings included dystrophic nails (12%), Beau's lines (10%), clubbing (10%), brittle nails (8%), onychomycosis (5%) and longitudinal melanonychia (5%).…”
Section: Hepatitis C 7%mentioning
confidence: 50%
“…16 In a study done by Salem et al, 18% of the patients had onychomycosis, 10% of the patients had brittle nails, 7% cases had clubbing and 6% had dystrophic nails. 19 Gavli et al found Terry's nails in 75% cases followed by onychomycosis in 50% cases. 15 Muehrcke's nails were not reported in the studies done by Salem et al, Niaz et al and Gavli et al 14,15,19 50% of the patients in our study had hair changes and some had more than one change.…”
Section: Hepatitis C 7%mentioning
confidence: 97%
See 1 more Smart Citation